Minority Students in Graduate Studies: An Exploration into Women's Accessibility to Higher Education through the Open and Distance Learning Mode in Nigeria - Vincent Ado Tenebe; Olugbenga D. Ojo; Yemisi I. Ogunlela; Anthonia B. Yakubu; Dorothy Ofoha (West African Journal of Open and Flexible Learning)
Despite the odds militating against women education in a patriarchal society like Nigeria, an increasing number of women are pursuing higher education studies. This study focuses on women in difficult circumstances constrained by socio-cultural factors who are pursing postgraduate programmes through the open and distance learning (ODL) mode, herein referred to as minority women, which include women in purdah, women in remote and rural communities, women in full-time employment, single-parent women, underprivileged women, and women traders. Despite being a disadvantaged group, not much is known about the experiences and live stories of these women and how they manage to wade through the rigours of graduate studies notwithstanding the many obstacles they face. To fill this gap in knowledge, the present study aimed at developing insight into the experiences of these women including their challenges, coping strategies, sources of motivation, as well as their attitudes and perceptions toward self and in relation to their social status. A sample of 82 minority women students took part in the study. They were purposively selected study centres of the National Open University of Nigeria. The study employed a qualitative research approach utilizing focus group discussion method and personal accounts for data generation. Data collected were analysed using the thematic analysis approach. Several remarkable findings emerged from the study pointing to factors that could motivate the minority women students to rise above their limitations toward achieving their full potentials and the significant role of ODL in facilitating this process. It is hoped that the study would be a source of inspiration to many others especially girls and women towards increased accessibility to higher education.